Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Keputusan Investasi Mahasiswa di Tasikmalaya - Riza Amalia; Dheri Febiyani Lestari (PT. Alahyan Publisher Sukabumi, 2026)
This study aims to analyze the influence of financial literacy and financial behavior on investment decisions of students in Tasikmalaya. The main focus of the study is to evaluate the extent to which financial understanding and individual financial management skills can improve the quality of investment decision-making. This study used a quantitative method with a cross-sectional survey approach. Data were collected through questionnaires distributed to 100 student respondents in Tasikmalaya selected using a purposive sampling technique. The data analysis technique used was multiple linear regression with the help of SPSS version 27 software. The results of the analysis revealed that financial literacy and financial behavior have a positive and significant influence on investment decisions. The research model achieved a coefficient of determination (R²) of 70.8%, indicating a strong ability to explain variations in student investment decisions that are not only influenced by financial understanding but also disciplined and measured financial management. Implications of this study include the development of more effective financial education programs to increase investment involvement among students.